2015
DOI: 10.3389/fenrg.2015.00049
|View full text |Cite
|
Sign up to set email alerts
|

Net-Energy Analysis of Integrated Food and Bioenergy Systems Exemplified by a Model of a Self-Sufficient System of Dairy Farms

Abstract: Agriculture is expected to contribute in substituting of fossil fuels in the future. This constitutes a paradox as agriculture depends heavily on fossil energy for providing fuel, fodder, nutrients, and machinery. The aim of this paper is to investigate whether organic agriculture is capable of providing both food and surplus energy to the society as evaluated from a model study. We evaluated bioenergy technologies in a Danish dairy-farming context in four different scenarios: (1) vegetable oil based on oilsee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Allocating part of the cereal area to green manuring in order to produce feed for biogas production resulted in a decreased area for cereal production. Similar results were published by Pugesgaard et al (2014) and Markussen et al (2015) who found that allocating part of the land to energy production decreased the total output of food. However, if grasses are cultivated on less productive fields or if yields are increased by improving soil fertility, the impact is not as great as the share of the reduced cereal area would imply.…”
Section: Discussionsupporting
confidence: 89%
“…Allocating part of the cereal area to green manuring in order to produce feed for biogas production resulted in a decreased area for cereal production. Similar results were published by Pugesgaard et al (2014) and Markussen et al (2015) who found that allocating part of the land to energy production decreased the total output of food. However, if grasses are cultivated on less productive fields or if yields are increased by improving soil fertility, the impact is not as great as the share of the reduced cereal area would imply.…”
Section: Discussionsupporting
confidence: 89%
“…Allocating part of the cereal area to green manuring in order to produce feed for biogas production resulted in a decreased area for cereal production. Similar results were published by Pugesgaard et al (2014) and Markussen et al (2015) who found that allocating part of the land to energy production decreased the total output of food. However, if grasses are cultivated on less productive fi elds or if yields are increased by improving soil fertility, the impact is not as great as the share of the reduced cereal area would imply.…”
Section: Biomass Production For Food and Energysupporting
confidence: 88%
“…Currently, the production of biofuel from crops still requires the use of fossil fuels during crop production (Dalgaard et al, 2001), and other factors including various social, economic, environmental and technical issues need to be overcome to make the production process more sustainable (Oumer et al, 2018). However, biofuel production from OSR has been calculated to have a positive net energy balance (Kusek et al, 2016) and can also contribute towards circular, self-sufficient systems in terms of energy requirements (Markussen et al, 2015).…”
Section: Eu Biofuels Policymentioning
confidence: 99%